REKAYASA PERANGKAT LUNAK PRODUK INOVASI, HAK KEKAYAAN INTELEKTUAL, DAN INKUBATOR BISNIS DENGAN METODE USER CENTERED DESIGN: STUDI KASUS UNIVERSITAS BINA DARMA - Ifran Wahyudi; Ari Muzakir (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2020)
Abstract : The Directorate of Innovation and Business Incubator is part of Bina Darma University which facilitates tenants to get incubations from partners who collaborate with Bina Darma University. This research was conducted with the aim of creating an information system that can solve existing problems, namely building a web-based information system and Progressive Web Apps (PWA) using the Codeigniter and Materialize framework, which is an information system designed to manage all data collection. Tenants, activity data collection, document storage, and other data in the Directorate of Innovation and Business Incubator, and can display the required information reports quickly and efficiently. By using the Focus Group Discussion (FGD) method, researchers get feedback from clients by discussing, and researchers can create systems with the best implementation to meet client needs. The results of this study are the availability of a information system that can assist users in managing all tenant data collection, activity data collection, documentation, and data on innovation products and intellectual property rights at the Directorate of Innovation and Business Incubator at Bina Darma University.